The letter of Mara bar Sarapion in context : proceedings of the symposium held at Utrecht University, 10-12 December 2009 - Merz, Annette.; Tieleman, Teun. (Culture and History of the Ancient Near East, 2012)
The Letter of Mara bar Sarapion to his son - preserved in a single Syriac manuscript (7th. century CE) - still speaks to its readers, evocatively depicting the dramatic situation of a nobleman imprisoned after the Roman capture of Samosata, capital of Commagene. The letter is best known today for a passage on the "wise king of the Jews," which may be one of the earliest pagan testimonies concerning Jesus Christ. Ongoing controversy over the letter's date, nature, and purpose has, however, led to the widespread neglect of this intriguing document. In the present volume, Merz and Tieleman have brought together cutting-edge research from an interdisciplinary team of leading experts that significantly advances our appreciation of the letter and its historical context.